FROM BROWSING TO BUYING: EXPLORING AI’S TRANSFORMATIVE IMPACT ON ONLINE SHOPPING IN INDIA - MacLeod, Alexander James; O’Neill, Emily Anne (Ayden Journal of Management and Social Sciences, 2024)
Artificial intelligence (AI), characterized by machines mimicking cognitive functions akin to human minds, has garnered significant attention and investment globally, including in India. This review explores the evolution and increasing prevalence of AI in India, particularly amidst the backdrop of the global pandemic. Drawing insights from authoritative sources such as "Artificial Intelligence: A Modern Approach (AIMA)" by Russell and Norvig (2020) and a study conducted by PwC India, it delves into the rapid adoption of AI technologies across various industries. Notably, India has witnessed a remarkable surge in AI usage, surpassing developed countries like the US, UK, and Japan, with a 45% increase during the pandemic. This review highlights the transformative potential of AI in India and underscores the need for continued investment and research to harness its benefits fully.